Postconcussion syndrome (PCS) in the emergency department: predicting and pre-empting persistent symptoms following a mild traumatic brain injury. Issue 1 (6th March 2013) - Reuben, Adam; Sampson, Paul; Harris, Adrian Ralph; Williams, Huw; Yates, Phil
Abstract : Head injuries across all age groups represent an extremely common emergency department (ED) presentation. The main focus of initial assessment and management rightly concentrates on the need to exclude significant pathology, that may or may not require neurosurgical intervention. Relatively little focus, however, is given to the potential for development of post-concussion syndrome (PCS), a constellation of symptoms of varying severity, which may bear little correlation to the nature or magnitude of the precipitating insult. This review aims to clarify the aetiology and terminology surrounding PCS and to examine the mechanisms for diagnosing and treating.